Better food security, nutrition and climate-resilience in Bangladesh. Project profile. - International Potato Center (International Potato Center, 2019)
Bangladesh’s fertile delta soils are suffering from increasing salinization, which threatens the lives and livelihoods of farmers and other inhabitants. This project helps increase farmers’ access to improved, salt-tolerant varieties of potato and sweetpotato, diversifying their production, and boosting their food security, nutrition, and climate resilience.